The influence on pass time and passes attempted qualify to second stage of FIFA World Cup 2010 in South Afrika - Saito, K.; Yoshimura, M. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Ball possessions and passing soccer are key words in a modern soccer. But, in the game analysis there are a few studies about the passing speed when passing is paid attention. Then, it was thought that there are a lot of passes attempted in actual play time if the passing speed is fast, and calculated the time required to hit one passing in this study. However, it is a rashness that that time is referred to as a passing speed. That time is represented as Pass Time, and actual play time is represented as Net Play Time in this study. This study aims to verify the difference between the not qualified teams and the qualified teams to 2nd stage in the passes attempted and the Pass Time at all group stage games of FIFA 2010 South Africa World Cup. Methods Pass Time is calculated by Net Playtime divided by passes Attempted. Pass Time of each team for the all Group stage games were calculated, and the analysis of all Group stage games was done. Results & Discussion It is found out that a lot of qualified teams show that there are a lot of passes Attempted and that Pass Time is smaller than not qualified teams. Moreover, It is found out that qualified teams to semi final show the same compared with the qualified teams to 2nd stage. Conclusion It is suggested that increasing passes attempted and lessening Pass Time are effective in order to be qualified teams to 2nd stage.